2018
DOI: 10.1177/0363546517753386
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Knee Kinematics After Anatomic Anterior Cruciate Ligament Reconstruction Is Dependent on Associated Meniscal Injury

Abstract: Associated medial meniscal injury in the setting of ACLR leads to increased ATT at 24-month follow-up. Furthermore, isolated anatomic ACLR in the absence of meniscal injury demonstrated no significant difference from native knee kinematics at 24-month follow-up during rigorous "high demand" knee activity with the current sample size. Patients undergoing anatomic ACLR in the presence of medial meniscal injury remained at a higher likelihood of sustaining altered long-term knee kinematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…Third, we conducted a weightbearing motion analysis under functional loading, which provided consistent kinematic patterns, such as squatting and kneeling. 16 When compared with step-up and sit-to-stand motions, a 1-leg lunge represents a more strenuous motion with high demand for knee function 1 and is a functional knee activity with a wide range of flexion. 53 Furthermore, the lunge motion is a commonly used rehabilitation exercise 7 and has been widely used as an assessment of in vivo ACL function before and after reconstruction surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we conducted a weightbearing motion analysis under functional loading, which provided consistent kinematic patterns, such as squatting and kneeling. 16 When compared with step-up and sit-to-stand motions, a 1-leg lunge represents a more strenuous motion with high demand for knee function 1 and is a functional knee activity with a wide range of flexion. 53 Furthermore, the lunge motion is a commonly used rehabilitation exercise 7 and has been widely used as an assessment of in vivo ACL function before and after reconstruction surgery.…”
Section: Discussionmentioning
confidence: 99%
“…11,17 Akpinar et al found that patients undergoing an anatomic ACL reconstruction in the presence of medial meniscal injury had a higher risk of experiencing altered long-term knee kinematics because of a greater anterior translation of the tibia. 18 The medial meniscus is exposed to higher shearing forces as it acts as a secondary stabilizer of the knee in patients with ACL injuries, leading to an increased risk of suffering chronic medial meniscus tears. 19 Moreover, a decreased medial meniscus posterior horn height has also been proposed as a risk factor for ACL graft rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effect of the residual laxity derived from medial meniscectomy on the ACL and the overall knee joint remains unknown. An elegant dynamic stereoradiographic study by Akpinar et al 3 showed an increased anterior tibial translation during downhill running even 24 months after ACL reconstruction in patients with medial meniscal lesion with respect to contralateral knee and isolated ACL reconstruction. However, the authors did not distinguish between the entity of meniscal lesion and, above all, its treatment.…”
Section: Discussionmentioning
confidence: 99%